IMPLEMENTASI PEMBINAAN MELALUI PROGRAM REHABILITASI DAN REINTEGRASI SOSIAL BAGI NARAPIDANA TERORISME - ., Maliki (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 2 (2013), 2013)
Coaching for terrorism inmates in institution is an effort to counter terrorism. Coaching is done through rehabilitation and social reiintegration. In this study there were two issues discussed the implementation of training for terrorism prisoners as well as the factors driving and inhibiting formation for terrorism prisoners. This type of research is empirical legal research. The research is descriptive. Primary data sourced from observation and interviews while secondary data sourced from literatures and electronic articles. Secondary data was collected through library research. Data is collected, processed and presented qualitative descriptive analysis. Coaching for terrorism inmates in prisons have not been implemented optimally. It can be seen from the formation of the terrorist network that carried out in prisons. Former inmates also returned to terrorism after being released from prison. The driving factor for the development of terrorist prisoners is because terrorism is a crime that should ditanggulagi. Guidance is also the mandate of Act Number 12 of 1995 Concerning Correctional Institution and the Indonesian Government Regulation Number 99 of 2012 concerning the Second Amendment to Government Regulation No. 32 of 1999 on Terms and Procedures for Implementation of the Right of Corrections Inmates and the vision and mission of the institution. Coaching effort is one of community protection movement. Coaching is a limiting factor in terms of the legal structure and legal culture. Prison staff lack the ability to Islam, a lack of awareness of officers, there is no coaching format for terrorism prisoners, the view that training for terrorism prisoners are tightening and the lack of specialized staff in fostering terrorism inmates. Legal culture includes cultural terrorist prisoners law does not regret his actions and legal culture society reject terrorism inmates.
Keywords: coaching; prisoners; terrorism; institution